Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1172/jci.insight.121479
|View full text |Cite
|
Sign up to set email alerts
|

Plasma copeptin and chronic kidney disease risk in 3 European cohorts from the general population

Abstract: INSERM and Danone Research Centre for Specialized Nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 60 publications
1
24
1
Order By: Relevance
“…Elevated concentrations of copeptin are prognostic markers in many clinical conditions, such as septic shock, pneumonia, cardiovascular disease, and diabetes (21)(22)(23). Furthermore, copeptin is elevated in CKD and proteinuria (24,25). Although this association could be attributed to decreased filtration by the kidneys, it has been shown that kidney clearance is not a main determinant of copeptin concentrations, because levels were unchanged in living kidney donors despite reduction in eGFR (26).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated concentrations of copeptin are prognostic markers in many clinical conditions, such as septic shock, pneumonia, cardiovascular disease, and diabetes (21)(22)(23). Furthermore, copeptin is elevated in CKD and proteinuria (24,25). Although this association could be attributed to decreased filtration by the kidneys, it has been shown that kidney clearance is not a main determinant of copeptin concentrations, because levels were unchanged in living kidney donors despite reduction in eGFR (26).…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies show that the higher the copeptin concentration, the higher the risk of decline of renal function and progression of CKD [16, 17]. Thus, Zittema et al in their study in IgA nephropathy patients found that a higher level of copeptin was associated with the severity and progression of the disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of chronic vasopressin secretion in the incidence and progression of diabetic and non-diabetic CKD has been recently highlighted in various clinical [8,9,10,11,12] and experimental studies [7,13]. Chronic stimulation and/or overexpression of vasopressin receptors V1a and V2 have been associated with renal and cardiac alterations, while chronic blockade of both receptors has provided beneficial effects [14,15,16].…”
Section: Introductionmentioning
confidence: 99%